MPEG transmission schemes for a timed token medium access control network. - Ng, Joseph Kee-Yin (Computer communication review.)
This paper presents three transmission schemes to improve the transmission of MPEG video over a timed token medium access control (MAC) network. Multiple classes of MPEG video are used in the study. These data are captured from real video programmes and we categorized these video clips according to their traffic burstiness and workload characteristics. The performance measure of the timed token MAC network is in terms of the maximum number of MPEG video streams being transmitted without any frame missing its deadline. This simulation study observed that by employing the Regulated Scheme, we could improve the performance by 28 to 40%. When applying the Grouping Scheme for the MPEG transmission, we can improve the performance between 142 and 149%. When we combined the two schemes together, the Regulated Grouping Scheme can further improve the performance up to 153% which is a dramatic improvement over the original transmission scheme.